2009
DOI: 10.1128/aem.01942-08
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Barotolerance, Thermotolerance, and Cellular Morphology throughout the Life Cycle of Listeria monocytogenes

Abstract: Changes in barotolerance, thermotolerance, and cellular morphology throughout the life cycle of Listeria monocytogenes were investigated. For part 1 of this analysis, L. monocytogenes ATCC 19115 was grown to log, stationary, death, and long-term-survival phases at 35°C in tryptic soy broth with yeast extract (TSBYE). Cells were diluted in whole milk that had been subjected to ultrahigh temperatures (UHT whole milk) and then high-pressure processed (HPP) at 400 MPa for 180 s or thermally processed at 62.8°C for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
49
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 51 publications
3
49
2
2
Order By: Relevance
“…2B) are observed as cocci in chains, yet no change in cell surface was observed. The change in the morphology of Listeria from a rod to a coccus has been shown to be based on the medium type and the presence of stress (temperature or pressure) (14). Figure 3 shows SEM of Mycobacterium sp.…”
mentioning
confidence: 99%
“…2B) are observed as cocci in chains, yet no change in cell surface was observed. The change in the morphology of Listeria from a rod to a coccus has been shown to be based on the medium type and the presence of stress (temperature or pressure) (14). Figure 3 shows SEM of Mycobacterium sp.…”
mentioning
confidence: 99%
“…3) in death phase may increase the general resistance of L. monocytogenes during and after death phase, as DnaK stabilizes proteins under various types of stresses (18). This may partly explain why LTS-phase cells of L. monocytogenes had significantly higher D values at 400 MPa than that at stationary phase (41). When listerial cells entered death phase, the majority of cells died, whereas about 10% of the population survived (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…The LTS phase was also observed in L. monocytogenes by Wen et al, during which the cell density was found to remain at ϳ10 8 CFU/ml in tryptic soy broth with yeast extract (TSBYE) for over 30 days (41). These LTS cells were found to be predominantly cocci and highly resistant to both heat and high pressure stresses (41). The mechanisms that trigger listerial cells to transit from bacilli to cocci during the LTS phase remain unclear yet intriguing.…”
mentioning
confidence: 77%
See 2 more Smart Citations